The music of the temporalists - Pogoriloffsky, André (GB CreateSpace Independent Publishing Platform, 2011)
A Parisian drugstore owner (André Pogoriloffsky), a man in his early fifties, who is also a skilled amateur piano player, experiences a two year long mental trip to a parallel (Temporalist) world, as an avatar. He will soon find out that he was purposely "imported" there in order to be taught the basics of that culture's music theory. Pogoriloffsky is permanently accompanied by a local musicologist Jean-Philippe, an expert in the European musical tradition and, for a while, initiated by an old psychologist (Herr Sch& etc.) in the cognitive aspects of Temporalist music theory. The two men ask Pogoriloffsky to memorize as much as he is capable to from the theoretical notions that he is presented with so that, once returned to Paris, be able to transcribe all that information for the use of his own musical culture.The music of the Temporalists describes a journey into a parallel world that is populated with humans like us who just happened to have cultivated music as "the art of time" and not as "the art of sounds". Pogoriloffsky recounts all that experience with honesty, doing his best to meet his two guides' expectations.